The Siğil of the Zenica Naib (1170-1173) As a Historical Source (Prilozi za orijentalnu filologiju, 2017)
This siğil represents the protocol of the Zenica naib who was an authorised representative of the Travnik qadi. It does not represent a continous entity, however, but a collection composed of several parts. The first document dates Ifom 1170 (1757.) and the last one from 1178. (1765.). It contains 182 documents of different contents: 14 sultans’ documents 31 bujruldias, 9 muraseles of the Travnik qadi, 3 ilams, 112 matrimonial contracts, 3 testamentary verdicts, as well as other documents conceming different affairs and events.The data contained in this siğil and in the other preserved sigils are an unavoidable source for studying the past of Zenica and for the study of cultural, economic, social and political history of that region.The original document from the Institut of Oriental Studies in Sarajevo was bumt down in 1992. đuring the agression on Bosnia-Herzegovina. Photocopies are in property of the autor.